Responding to the Coronavirus with Open Educational Resources - Wayne Rimmer (Cranmore Publishing, 2020)
Open Educational Resources (OER) are characterised by being available in the public domain under an open license, typically Creative Commons, so they can be copied, redistributed and reworked. The literature shows OER to be under-recognised in TESOL but the argument in this discussion paper is that the coronavirus provides an opportunity for OER to be integrated into the university curriculum. This is not simply because OER are free of cost, although this is not an insignificant advantage in an industry often under severe financial constraints, especially in a period of severe disruption as witnessed with the coronavirus. Of more significance are claims that the adoption of OER can enhance pedagogy. Three case studies are used to demonstrate the value of OER in coronavirus-affected university settings. The first is a personal scenario while the second and third are putative constructions of OER use. My own case study is of using OER to create an observation procedure to support instructors transitioning to online teaching. In the second study, OER are used to teach faculty how to write grant proposals. In the third, OER are a source for student oral presentations. This leads to reflection on the claims made for OER as regards pedagogy and the challenges they face The conclusion is that the impact of OER remains potential until the research base is fuller but at the very least the coronavirus represents a testing ground for raising awareness of and experimenting with OER.